Le discours mémoriel ottoman au musée naval d’Istanbul - Juliette Dumas (Revue des Mondes Musulmans et de la Méditerranée)
For more than a decade now, memorial uses of the Ottoman past have grown, hiding the fact that there exists an abundance of historical narratives, still understudied. This article aims to explore this by analyzing the narratives presented by the Naval Museum of Istanbul. Applied methodology focuses on exhibits and explanatory boards in rooms dedicated to the Ottoman period. Two main topics appear: the articulation of a Turkish-Ottoman-Istanbul synthesis and, the promotion of a power discourse concerning the Ottoman-Turkish naval forces. The narrative treatment of history remains deeply traditional presented from the top down with emphasis on heroic figures, epic battles and chronological histories loaded with important dates and tainted with strong nationalistic opinion. As a military institution, the Turkish naval power is assimilated to Ottoman naval power without any distinction for the historical discontinuities that mark these two epochs. Any discussion of military “decline” is avoided, and corsairs and martyrs glorified. Further, there is no mention of a social history for the Ottoman navy.